2009
DOI: 10.3176/eng.2009.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sintering techniques on the performance characteristics of steel-bonded TiC-based cermets

Abstract: This paper analyses the influence of sintering technology (temperature, gas compression during sintering) and heat treatment on the performance of an advanced TiC-based cermet developed for metalforming. The performance was evaluated by adhesive wear resistance, transverse rupture strength and microstructure studies. Optimal technology and parameters, ensuring maximum wear resistance and strength of the TiC-based (carbide) composite, are determined. The positive effect of gas compression during sintering on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…It is concluded that similarly to WC-Co hardmetals, the sinter/HIP technology enables improvements in the strength of low-binder cermets. Similar results were obtained for TiC-FeNi cermets [13,14].…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…It is concluded that similarly to WC-Co hardmetals, the sinter/HIP technology enables improvements in the strength of low-binder cermets. Similar results were obtained for TiC-FeNi cermets [13,14].…”
Section: Introductionsupporting
confidence: 87%
“…Side wear was measured by the contact method using the Mitutoyo STRATO-9-166 measuring machine as an average of five measurements. sinter/HIP and to the dependence of its parameters (temperature and gas compression during sintering) on the performance of the TiC-based cermet [14]. The main reason is that the porosity of the composites decreases.…”
Section: Key Engineering Materials Vol 527mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbide phase provides alloy with high strength, hardness and abrasion resistance, and steel binder phase provides alloy with the performance of heat treatment, machinability, forgeability and weldability. Therefore, the steel-bonded carbide is a new engineering material between alloy steel and cemented carbide, which are widely used in cutting tools, moulds, wear-resisting components and so on [2][3][4][5]. In this paper, a kind of TiC based high manganese steel-bonded carbide was developed.…”
Section: Introductionmentioning
confidence: 99%